Public support for tobacco control policy extensions in Western Australia: A crosssectional study - Rosenberg, M.; Pettigrew, Simone; Wood, L.; Ferguson, R.; Houghton, S. (B M J Group, 2012)
Objectives: Policy makers seeking to introduce new tobacco control measures need to anticipatecommunity support to assist them in planning appropriate implementation strategies. This studyassessed community support for plain packaging and smoking bans in outdoor locations in Australia.Design: Analytical cross-sectional survey. Setting and participants: 2005 Western Australianadults participated in a computer-assisted telephone interview. Random household telephone numberswere used to obtain a representative sample. Outcome measures: Support for plain packaging ofcigarettes and smoking bans at outdoor venues by demographic characteristics. Results: Around half of the survey respondents supported plain packaging and almost a further quarter reported being neutral on the issue. Only one in three smokers disagreed with the introduction of a plain packaging policy. A majority of respondents supported smoking bans at five of the six nominated venues, with support being strongest among those with children under the age of 15 years. The venues with the highest levels of support were those where smoke-free policies had already been voluntarily introduced by the venuemanagers, where children were most likely to be in attendance, and that were more limited in size.Conclusions: The study results demonstrate community support for new tobacco control policies.This evidence can be used by public policy makers in their deliberations relating to the introduction of more extensive tobacco control regulations.